Exploring Retributive School Discipline Practices in Ontario: Voices of the Suspended and Expelled - Rooney, Teagan (My University, 2017)
Through an analysis of 7, semi-structured, one-on-one, open-ended interviews and relying on methodological principles from interpretive social science (ISS) and critical social sciences (CSS) this graduate thesis uncovers the voices of youth who have been suspended and/or expelled from a public secondary school in Ontario. Youth in this study spoke to the impact that being suspended and/or expelled had on school climate through describing the adverse changes that they experienced in regards to their relationships with their peers, and school professionals. A unique contribution from my study is a participant’s description of an experience of suspension, which I interpreted as being caused by, the behavioural targeting of a student living with a disability. Many of the participants also explained how the use of disciplinary procedures that rely on sending a student home from school for x amount of days can affect students’ academic progress and success. Furthermore, the similarities between the treatment of disciplined students in the education system, and the treatment of criminal offenders in the justice system found in this study, included: the use of punitive discipline, increased surveillance, and the involvement of the police in disciplinary processes. The youth in this study recognize that the use of suspension and expulsion does not dig beneath the surface and address the root of the problem, and agree that this approach to school discipline is ineffective in regards to correcting behaviour. Finally, all of the youth in this study suggested the development and implementation of more supportive approaches to addressing and preventing unsafe and inappropriate behaviour in schools that aim to keep students in school while resolving the problem.
Keywords: school discipline; suspension; expulsion; youth; voice